Collaborative case conceptualization : working effectively with clients in cognitive-behavioral therapy - Kuyken, Willem, ....-; Padesky, Christine A., ....-; Dudley, Robert, ....- (London : The Guilford Press, 2011)
Presenting an innovative framework for tailoring cognitive-behavioral interventions to each client's needs, this accessible book is packed with practical pointers and sample dialogues. Step by step, the authors show how to collaborate with clients to develop and test conceptualizations that illuminate personal strengths as well as problems, and that deepen in explanatory power as treatment progresses. An extended case illustration demonstrates the three-stage conceptualization process over the entire course of therapy with a multiproblem client. The approach emphasizes building resilience and coping while decreasing psychological distress. Special features include self-assessment checklists and learning exercises to help therapists build their conceptualization skills.
Gedragstherapie